The Perceptual Constraints of Adult Learners on the Implementation of Adult Basic Education Programs in Kenya - Nzinga, Edward K. (Scholars Bulletin, 2017)
The objective establishes the perceptual constraints of adult learners on the implementation of adult basic education programs. The study used descriptive survey research design and was based on the conceptual framework embracing four main theories namely: - Adult learning theory, Mezirow‟s Theory of Perspective Transformation, Systems Theory and Reference Group Theory. The units of analysis were 424 Adult Education Learning Centres. The study population was 7104 adult education Learners. The targeted populations were 2304 Learners. The researcher used both Stratified and saturated random sampling to pick out a corresponding sample. The instruments of data collection were questionnaires, interviews and document analysis. Reliability of the instruments was addressed through piloting in one adult education centre and reliability co efficient of 0 .745 which indicated that the instruments were reliable were obtained by subjecting the instruments to a Split-half Technique and Spearman “Brown Prophesy Formula”. Data was analysed using both qualitative and quantitative methods. The findings show that if 2.92 (58.40%) of learners were asked to pay for adult education studies, he/she would gladly do so. Adult education programs suffer from stigmatization and hence potential learners find it almost an embarrassment to be involved in the program as attested by the score of 3.35 (67.04%). When an adult learner listens to what others say about adult education the adult learner felt encouraged to continue with the program. Every effort should be done by all the stakeholders in adult and continuing basic education to either reduce or get rid of the stigma associated with adult education since this affects both the learners and those that are charged with its supervision and monitoring.
Journal Article
Keywords: Perceptual Constraints; Adult Basic Education Programs; Adult Learners